Evaluation of acute plant toxicity, antioxidant activity, molecular docking and bioactive compounds of lemongrass oil isolated from Omani cultivar - Haneen Al Weshahi; Mohammad Sohail Akhtar; Salem Said Al Tobi; Amzad Hossain; Shah Alam Khan; Alia Bushra Akhtar; Sadri Abdullah Said (Toxicology Reports)
Lemongrass (Poaceae) is one of the aromatic plants with strong odors. Traditionally, lemon grass oil has been used for the treatment of many diseases such as gastrointestinal cramps, high blood pressure, high body temperatures, and fatigue, and is also considered an antibacterial and anti-diarrheal agent. Therefore, this study aims to investigate volatile active constituents and a few important biological activities of the volatile oil of lemongrass (Cymbopogon citratus) grown in Oman. To support the results of experimental studies, and to find out the main active constituents responsible for exhibiting biological activities molecular docking studies have also been performed. A sufficient amount of essential oil was obtained using steam distillation from fresh leaves of lemongrass. Volatile constituents were identified with the GC-MS analysis. Lemon grass oil exhibited a very good in vitro antioxidant activity (65.08–90.48 % inhibition of DPPH) with increasing concentration (31.25–1000 µg/mL) of oil. Isolated oil also exhibited good cytotoxic activity against the brine shrimps (100 % mortality at 1000 mcg/mL). Furthermore, molecular docking studies confirmed that beta citral is the monoterpene compound responsible for antioxidant and cytotoxic activity.